The ratio of contrast volume to glomerular filtration rate predicts in-hospital and six-month mortality in patients undergoing primary angioplasty for ST-elevation myocardial infarction - (:unkn) unknown (My University, 2015)
Background: The aim of this study is to determine the impact of ratio of contrast volume to glomerular filtration rate (V/GFR) on development of contrast-induced nephropathy (CIN) and long-term mortality in patients with ST-segment elevation acute myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Methods: A total of 645 patients with STEMI undergoing primary PCI was prospectively enrolled. CIN was defined as an absolute increase in serum creatinine > 0.5 mg/dL or a relative increase > 25% within 48 h after PCI. The study population was divided into tertiles based on V/GFR. A high V/GFR was defined as a value in the third tertile (> 3.7). Results: Patients in tertile 3 were older, had higher rate of smoking, diabetes mellitus and CIN, lower left ventricular ejection fraction, hemoglobin, and systolic and diastolic blood pressure compared to tertiles 1 and 2 (p < 0.05). V/GFR was found an independent predictor of in-hospital and 6-month mortality. We found 2 separate values of V/GFR for 2 different end points. While the ratio of 3.6 predicted in-hospital mortality with 78% sensitivity and 82% specificity, the ratio of 3.3 predicted 6-month mortality with 71% sensitivity and 76% specificity. Survival rate decreases as V/GFR increases both for in-hospital and during 6-month follow-up. Diabetes mellitus and multivessel disease were other predictors of in-hospital mortality. Conclusions: High V/GFR level is associated with increased in-hospital and long-term mortality in patients with STEMI undergoing primary PCI.